Evaluation of the merits of two drugs-dexmedetomidine and ketamine for day care hysteroscopic procedures - Sen, Jayashree; Sen, Bitan (International Journal of Research in Medical Sciences, 2019)
Background: The aim was to compare the hemodynamic changes intra operatively and to ascertain the superior efficacy of the study drugs Dexmedetomidine, a highly selective alpha-2-adrenoceptor agonist having sympatholytic, dose dependent sedation, analgesic properties, amnestic effect without respiratory depression and Ketamine, a n-methyl-d-aspartate receptor antagonist, a dissociative sedative hypnotic with potent analgesic properties and marked sympathomimetic effects, have been taken for day care (ambulatory) hysteroscopic procedures. The objectives are to evaluate the requirement of rescue sedative and /or analgesic during the procedure and any complication of the drugs per-operatively. Methods: About 25 patients in each group in the range of age 20 to 55 years, weight 40-60 kg, height 145-155 cm, ASA I and II were injected with dexmedetomidine (D) 100 µg IV or Ketamine (K) 75 mg IV both over 10 mins at the onset of the procedure. Maintenance of anaesthesia had been done on mask ventilation with 30% oxygen and 70% nitrous oxide. Results: The demographic data was statistically insignificant. The haemodynamics were stable in the group D, not in group K, ‘p’ value <0.0001. The request for rescue sedation propofol and rescue analgesic fentanyl and the number of top up doses were higher in the group K, p’ value <0.01, statistically highly significant. Group K had suffered more per-operative complications. Conclusions: Dexmedetomidine for day care hysteroscopic procedures can be the anaesthetic drug of choice.